Web application with spatio-temporal analytics on soccer game data - Sin, Bryan Chong Wen (Nanyang Technological University, 2021)
As previous methods to process data collected from sports games and retrieve similar plays are too inefficient and ineffective, a new method called play2vec was devised to improve on past methods and tackle their shortcomings. In this Final Year Project, a web application that integrates play2vec into its core logic is created for users to retrieve similar plays within the same dataset provided.